The effect of home-based hypertension screening on blood pressure change over time in South Africa - Sudharsanan, Nikkil; Chen, Simiao; Garber, Michael G.; Bärnighausen, Till; Geldsetzer, Pascal (Health affairs, 2020)
There is considerable policy interest in home-based screening campaigns for hypertension in many low- and middle-income countries. However, it is unclear whether such efforts will result in long-term population-level blood pressure improvements without more comprehensive interventions that strengthen the entire hypertension care continuum. Using multiple waves of the South African National Income Dynamics Study and the regression discontinuity design, we evaluated the impact of home-based hypertension screening on two-year change in blood pressure. We found that the home-based screening intervention resulted in important reductions in systolic blood pressure for women and younger men. We did not find evidence of an effect on systolic blood pressure for older men or on diastolic blood pressure for either sex. Our results suggest that home-based hypertension screening may be a promising strategy for reducing high blood pressure in low- and middle-income countries, but additional research and policy efforts are needed to ensure that such strategies have maximum reach and impact.